Pengaruh Faktor Makroekonomi Terhadap Naik Turunya Nilai Saham Studi Pada Bank Rakyat Indonesia - Agustin Azizatuz Zahro; Arina Pramudita; Aziza Karunia Azhari; Muhammad Fahmi Nazari; Muhammad Aldi Maulana; Robi Pramana Putra; Sinta Ayu Purnama Sari (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The aim of this research is to evaluate the influence of macroeconomic factors such as interest rates, inflation and exchange rates on the movement of Bank Rakyat Indonesia (BBRI) share prices in the period 2020 to 2024. The analysis used is a quantitative method taking a multiple linear regression approach. The data used is secondary, obtained from other sources, namely the Indonesian Stock Exchange (BEI) and Bank Indonesia (BI). The analysis was carried out using multiple linear regression using EViews 12 software. The findings from the analysis show that the three independent variables do not have a significant impact on BBRI share price fluctuations, both in simultaneous and partial analysis. From the results of the analysis, it can be concluded that there is a relationship where interest rates and exchange rates have a significant positive influence on stock prices, while inflation shows a negative impact on share prices.